THE SOCIO-MATERIAL POWER OF COAL: THE DOWNSTREAMIZATION OF COAL AND THE ENERGY TRANSITION CHALLENGE - Abisono, Fatih Gama (Universitas Negeri Semarang, 2024)
Under the Paris Agreement in 2015, many countries are adaptive to the issue of climate change, especially the energy transition agenda through coal phasing out. However, the issue of coal phasing out has not received enough attention from energy issue researchers. Although as one of the largest coal producing countries in the world, Indonesia faces major challenges for the purpose of mitigating climate change. Under Joko Widodo's government, the situation was responded to with the coal downstream policy. Departing from the formulation of the research problem, the research question of this study: how does downstreamization of coal answer the challenge of low carbon in the middle of coal dominance? The purpose of this study is to test the relevance of coal in answering the challenges of energy transition. This study is an explanatory-qualitative research by using a case study approach strategy with the Jokowi administration's coal phasing out agenda case with a documentation study technique. The results of the research show the increasing importance of coal in driving the energy transition. The relevance is made possible because coal is the country's main support to encourage energy transition with the downstreamization of coal. In this case, the materiality of the biophysical character of the resource allows coal to create a new space in the form of a link in the supply chain of the national energy system in the context of a low carbon economy. The coal material ultimately contains the socio-material power that determines the energy transition.